Telekom Malaysia Berhad Challenges In Business Operation And Performance - Hassan, Hashim (2001)
This study is to undertake the analysis and detail study of the business operational performance of Telekom Malaysia Berhad. In particular, the issues on deterioration of the current company financial and operational performance as compared to the previou